(untitled) (Annals of Medical Research, 2021)
Aim: The most seen complication of multiple myeloma (MM) is renal insufficiency (RI). Although MM is known as one of the causes of reversible end-stage renal disease, these patients are usually not suitable for autologous stem cell transplantation (ASCT). We aimed in this study to reveal the clinical course of MM patients with renal insufficiency that underwent ASCT. Materials and Methods: We included 25 MM patients with RI who has undergone ASCT in this study. Creatinine levels more than 2 mg/dL was defined as renal insufficiency at the time of diagnosis. For survival analysis, we included patients with a minimum 100 days post-transplantation follow-up. Results: Median age was 56.6±7.9 (42-65) years. Melphalan was given 140 mg/m 2 . Nine patients (36%) required dialysis at the time of diagnosis. Six patients became dialysis-free with induction therapy. After ASCT, none of the patients needed dialysis. Cox regression analysis showed a significant increase in disease-free survival (DFS) and overall survival (OS) times compared to patients with very good partial response in patients with complete response on the 100 th day of ASCT (for DFS; 15.7 months vs 63.7 months, p=0.009 and for OS; 37.9 months vs 97.3 months p=0.01, respectively). Conclusion: There are studies showing that ASCT performed with reduced dose of melphalan is a renal protective and effective method in patients with renal impairment. Our study confirms this thesis, as well as emphasizing the significant effect of CR on DFS and OS on the 100 th day after transplantation in these patients.